The Effect of E-Service Quality on Customer Satisfaction (A Study on Go-Jek Users) - HARSONO, GIAN FEBRI (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the effect of e-service quality on satisfaction of Go-Jek users in Malang. This explanatory research explains causal relationship between variables through hypothesis testing. The e-service quality variables used in this research are appearance, interactivity, informativeness, security, reliability, and responsiveness.From the population of university students in Malang who use Go-Jek application, 215 people who were at least 17 years of age and had used Go-Jek at least twice were selected as the sample. The instruments of this research were assessed using validity test, reliability test, and classical assumption test. The hypothesis testing was conducted using F test and t test, and the data were analyzed using multiple linear regression analysis.The result of this study shows that e-service quality variables consisting of appearance, interactivity, informativeness, security, reliability, and responsiveness influences the satisfaction of Go-Jek users in Malang.Keywords: E-Service, Customer Satisfaction